Evaluation of maxillofacial injury in the central part of Nepal - Biswari, G; Khanal, A; Gupta, P; Bansal, P (Journal of College of Medical Sciences-Nepal, 2012)
An evaluation of dental and maxillofacial trauma in College of Medical Sciences, Teaching Hospital, Bharatpur, Nepal was carried out to assess the causes of trauma and the relationship between the injuries to the Patient's Age, Gender, Type, Site of injury and the Influence of Alcohol from June 1, 2008 to May 31, 2011. Files of 1986 trauma patients were reviewed. Maxillofacial or dental injuries were observed in 269 (13.54%) of the trauma patients, caused by road traffic accidents 173 (64.3%), fall injury 43 (16.0%), physical assault 25 (9.3%), animal attack 9 (3.3%) and sport injury 19 (7.1%) Men were hospitalized almost three times more than women, most common site of injury was dentoalveolar fracture 79(29.37%) young people were at greater risk. The most frequent age of trauma was 15-29 years (51.7%). DOI: http://dx.doi.org/10.3126/jcmsn.v7i3.6702 Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-3, 11-16